The development of the quality of university life index for UiTM students / Kuldip Singh … [et al.] - Singh, Kuldip; Maghar Singh, Baljinder Singh; Augistine, Elizabeth Caroline (2010)
Universities are now are required to be responsive to students' expectations To be a university of choice, university administrators need to understand student experiences in their university and how to improve them so that a positive image will be portrayed to prospective students. Therefore measuring student's university experience is vital. The main objective of this paper is to examine student' perceptions about their university experience. A survey research design was used in this study to investigate student's university experience. The instrument developed and used for this study was adapted from the Monash Experience Questionnaire (M EQ) and Melbourne Experience Survey. Adaptations were made to make it suitable lor UiTM culture. Factor analysis resulted in 66 items being chosen and they were grouped into 8 dimensions, comprising (I) Skills Development, (2) Program Quality, (3) Student Support, ( 4) Teaching Quality, (5) Learning Environment and Resources , (6) Learning Community, (7) Academic Guidance and (8) Campus Experience. Stratified random sampling technique was employed to select the sample for the study based on the sampling frame obtained from each of UiTM's campus.